Next-generation probiotics - Barbosa, Joana Cristina (2022)
In the last years, the scientific community has recognized that specific microbial strains resident in the intestinal ecosystem play a key role in human health, participating in several functions beneficial to the host. Such microorganisms have been termed as next-generation probiotics and they are presently considered as food/nutraceutical supplements and biotherapeutic products. However, most of the next-generation probiotic candidates are nutritionally demanding and highly sensitive to aerobic conditions, which translates into several technological challenges concerning large-scale production and appeals to the development of suitable delivery systems able to promote viability and functionality of such probiotic strains. In this chapter, we will present an overall perspective of next-generation probiotics candidates in terms of their health beneficial effects, the delivery systems developed and employed to protect them, and related regulation framework and risk assessment targeting relevant criteria for commercialization in food and pharmaceutical markets.